Analysis of the Determinants of Poverty Among the Productive-Age Population in Rokan Hilir Regency - Surya, Rafqi Ardiansyah (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Poverty is a condition in which individuals are unable to meet a decent standard of living, and it remains a major development issue in many regions. Efforts to reduce poverty are often difficult to achieve if inappropriate approaches are applied. Therefore, optimizing the potential of the population, particularly those in the productive age group, is a key strategy in poverty alleviation. This study aims to analyze the effects of education level, employment status, savings ownership, mobile phone ownership, and health complaints on the poverty level of the productive-age population in Rokan Hilir Regency in 2024. The method employed is binary logistic regression. The findings reveal that employment status and health complaints have a significant influence on poverty. Individuals who work in non-casual employment are less likely to experience poverty compared to casual workers. In addition, productive-age individuals without health complaints are also less likely to fall into poverty. Based on these findings, it is recommended that the local government increase the creation of formal job opportunities and strengthen public health services, particularly for the productive-age population. Such policies are expected to sustainably reduce poverty rates in Rokan Hilir Regency.